A Robust Fungal Allomelanin Mimic: An Antioxidant and Potent π‐Electron Donor with Free‐Radical Properties that can be Tuned by Ionic Liquids. Issue 9 (6th June 2019) - Manini, Paola; Lino, Valeria; Franchi, Paola; Gentile, Gennaro; Sibillano, Teresa; Giannini, Cinzia; Picardi, Emanuela; Napolitano, Alessandra; Valgimigli, Luca; Chiappe, Cinzia; d'Ischia, Marco
Abstract: Developing effective strategies to increase the chemical stability and to fine‐tune the physico‐chemical properties of melanin biopolymers by rational control of π‐electron conjugation is an important goal in materials science for biomedical and technological applications. Herein we report that poly‐1, 8‐dihydroxynaphthalene (pDHN), a non‐nitrogenous, catechol‐free fungal melanin mimic, displays a high degree of structural integrity (from MALDI‐MS and CP/MAS 13 C NMR analysis), a strong radical scavenging capacity (DPPH and FRAP assays), and an unusually intense EPR signal (g=2.0030). Morphological and spectral characterization of pDHN, along with deassembly experiments in ionic liquids, indicated amorphous aggregates of small globular structures with an estimated stacking distance of 3.9 Å and broadband absorption throughout the visible range. These results indicate that DHN‐based melanins exhibit a high structural integrity and enhanced antioxidant and free‐radical properties of potentially greater biomedical and technological relevance than for typical indole‐based eumelanins. Abstract : Intense antioxidant : Biomimetic oxidation of 1, 8‐dihydroxynaphthalene (1, 8‐DHN), the monomer precursor of Aspergillus allomelanin, leads to a black and insoluble melanin‐like polymer with potent antioxidant activities and an unusually intense EPR signal that subject to modulation by deassembly in ionic liquids.